Formicidae di Lingkungan Kampus Universitas Islam Al-Azhar - Syuhriatin Syuhriatin; Slamet Mardiyanto Rahayu (bionature, 2020)
Abstract. Indonesia has abundant biodiversity, including ants (Formicidae). This study aims to determine the genus of Formicidae members in the garden of Al- Azhar Islamic University (Unizar), Mataram, West Nusa Tenggara. The research was conducted by using the exploration method. Based on the research, there are 4 (four) genera of Formicidae members in the Al-Azhar Islamic University (Uniar) Park, Mataram, West Nusa Tenggara, namely: Anoplolepis, Paratrechina, Odontoponera, and Lophomyrmex.Keywords: Formicidae, characteristics, Al-Azhar Islamic University